Normative, Atypical or Deviant? Interpreting Prehistoric and Protohistoric Child Burial Practices Interpreting Prehistoric and Protohistoric Child Burial Practices - Murphy, Eileen; Roy, Mélie Le (2023)
Normative, Atypical or Deviant? Interpreting Prehistoric and Protohistoric Child Burial Practices, the tenth volume in the SSCIP monograph series, explores the response of the living when dealing with the death of a child. This response is strongly connected to belief systems and concern for the fate of the deceased in the afterlife. The funerary rituals for each culture generally follow a prescribed format that will both satisfy the needs of the dead and ensure there are no negative consequences for the living. But how do we interpret burials that do not adhere to the recognised formula for their society? Can we find evidence that such differences involved positive or, indeed, negative emotions? Should atypical rites for children actually be considered normal since they are typical for their age cohort, differing only from those of adults, and perhaps simply reflect adult-centric interpretations of the past? The papers within the volume discuss these issues by focusing on juvenile burial practices in Europe and the Near East during recent prehistory and protohistory. The interpretation of normative, atypical or deviant is interrogated based on the context of the burials and the intentionality of the practice.